Use of the Bruininks-Oseretsky Test of Motor Proficiency, second edition in school practiceTrends in Sport Sciences: formerly Studies in Physical Culture and Tourism 2018 Vol.25 No.4 - Šeflová, Iva; Kalfiřt, Luděk; Indráčková, Karolína (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical inactivity is a global public health problem. One of the most important factors, which influence the later participation of children in regular physical activities, is sufficient movement competence level. The Bruininks-Oseretsky, 2nd version, test is considered the most comprehensive diagnostic tool for estimation of motor proficiency. It is used in the field of psychomotricity diagnostics in the Czech Republic. However, there are no Czech normative criteria. Aim of Study. The aim of this study is to investigate the usefulness of the Bruininks-Oseretsky Test of Motor Proficiency, 2nd version for both diagnostic and evaluative purposes in school practice. Material and Methods. The research sample was made of 45 primary school children (23 girls and 22 boys) of average age 9.2 ± 1.4 years. For the estimation of a motor proficiency we used the Bruininks-Oseretsky test, 2nd version – complete form with German normative criteria. Results: According to the total motor composite performance on BOT™-2, we found 16.7% of children with severe motor difficulties. It can identify the presence of developmental coordination disorder which requires necessary motor intervention. 28.6% of children were in the parameter total motor composite below the average with a risk of motor difficulties. In total, 72% of children had the BOT™-2 score in the 50th percentile or lower. Conclusions. The test is useful and suitable for recognizing signs of different kinds of developmental coordination disorders in school practice. Teachers need to undertake a course to be able to use this test. It is not easy to assess the test battery. The time required for the completion of the test may be too much for some of the children (over 60 minutes). That is why it is recommended to split the test battery into more parts.
Keywords: Bruininks-Oseretsky test; psychomotricity; motor proficiency